Strategi Humas Kwartir Daerah Gerakan Pramuka Jawa Timur dalam Membangun Citra Organisasi (The Commercium, 2022)
Scout Movement is organization that focuses on building character of young people. In 2013 curriculum, Scout Movement included as mandatory extracurricular at primary and secondary school. However, people assume that Scout Movement is not in line with organization’s expectations. Based on this reason, Scout Movement needs to build a good image in society. This study aims to find out the strategy from public relations of East Java Scout Movement provincial council in building an organizational image. This study used a descriptive qualitative approach with case study research methods. Data was collected through interviews, observation, and documentation. This study results showed that Public Relations of East Java Scout Movement Provincial Council used several strategies to build an organizational image, namely the strategy of publication, event, and news. Publication strategy was conducted through online, electronic, and print media. Event strategy included activities that provided benefits to the community. News strategy was conducted through online, electronic, and print media.